2007
DOI: 10.1007/s00418-007-0283-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved antigen retrieval in freeze-fracture cytochemistry by evaporation of carbon as first replication layer

Abstract: The recently developed freeze-fracture replica immunolabeling technique uses sodium dodecyl sulfate to clean replicas obtained from chemically unfixed, rapidly frozen cells by evaporation of platinum as first and carbon as second replication layer. The detergent dissolves remains of cellular material with the exception of components which are in direct contact to the replica film. Membrane lipids and membrane protein complexes of the protoplasmic and the exoplasmic membrane halves remain attached to the replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…We have noticed that labeling for ganglioside GM1 is drastically improved when the evaporation order is reversed, i.e., by evaporating C Wrst followed by Pt/C (Fujita et al 2007); a similar result was reported for some proteins (Masugi-Tokita et al 2007;Schlormann et al 2007). Why this improvement occurs by changing the order of evaporation has not been studied to date.…”
Section: Introductionsupporting
confidence: 60%
“…We have noticed that labeling for ganglioside GM1 is drastically improved when the evaporation order is reversed, i.e., by evaporating C Wrst followed by Pt/C (Fujita et al 2007); a similar result was reported for some proteins (Masugi-Tokita et al 2007;Schlormann et al 2007). Why this improvement occurs by changing the order of evaporation has not been studied to date.…”
Section: Introductionsupporting
confidence: 60%
“…Frozen slices were knife-cleaved in either a JEOL/RMC JFD 9010C or JFD II freeze-fracture device equipped with a −170°C liquid-nitrogen-cooled specimen cryoshroud and a liquid-helium-cooled cryopump (Rash and Yasumura, 1999). Freeze-fractured samples were either coated with 1-5 nm of carbon before replication [to increase labeling efficiency (Fujimoto, 1995; Schlörmann et al, 2007) but also decreases image resolution], or were replicated with 1-2 nm of platinum immediately after fracture (Rash and Yasumura, 1999). All replicated samples were stabilized by coating with 10-20 nm of carbon; the samples were removed and placed into a liquid nitrogen-cooled-cooled chamber that maintained the atmosphere at ca.…”
Section: Methodsmentioning
confidence: 99%
“…In recent investigations we established and enhanced the freeze-fracture immunolabeling technique according to Fujimoto (1997) in order to study the caveolin distribution at plasma membrane caveolae (Westermann et al 2005;Schloermann et al 2007). In the technique, sodium dodecyl sulfate (SDS) was used to clean freeze-fracture replicas obtained from chemically unWxed, rapidly frozen cells.…”
Section: Resultsmentioning
confidence: 99%